2018
DOI: 10.3892/mmr.2018.9462
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of virulence diversity of 73 Helicobacter�pylori strains isolated in Guizhou province, China

Abstract: The present study aimed to investigate the virulence diversity of Helicobacter pylori (H. pylori) in major ethnic groups residing in Guizhou province, China, and its association with clinical outcomes. Gastric mucosal biopsies were collected from the pylorus of patients with gastrointestinal disorders. H. pylori was identified by colonial morphology, Gram staining, a urease test and H. pylori‑specific 16S rRNA gene fragment PCR amplification. DNA was extracted from pure culture and used for virulence gene anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In Western countries, CagA+ strains comprise 50-60% of the HP+ population, and in the Chinese population, CagA+ strains occupy nearly 100% of the HP+ population [32,33]. Studies investigating the CagA status of Chinese HP strains with polymerase chain reaction (PCR) detected CagA genotypes in nearly all strains [34,35]. Considering the high CagA positivity in the Chinese HP+ population, the sperm concentration and motility should be weakened in HP+ patients, but the present study showed stable parameters.…”
Section: Discussionmentioning
confidence: 50%
“…In Western countries, CagA+ strains comprise 50-60% of the HP+ population, and in the Chinese population, CagA+ strains occupy nearly 100% of the HP+ population [32,33]. Studies investigating the CagA status of Chinese HP strains with polymerase chain reaction (PCR) detected CagA genotypes in nearly all strains [34,35]. Considering the high CagA positivity in the Chinese HP+ population, the sperm concentration and motility should be weakened in HP+ patients, but the present study showed stable parameters.…”
Section: Discussionmentioning
confidence: 50%
“…Similarly, when the combination of the s and m alleles of vacA is analyzed, the prevalence also differs. The vacA m1 allele is common in North Asian countries, including Japan and South Korea, whereas the m2 allele is predominant in Southeast Asia, including Taiwan, China, and Vietnam [ 36 ]. Interestingly, in this study, the vacA s1m1/s2m2/cagA+ genotype in both the antrum and corpus was detected in one patient, and the vacA s1m1/s1m2/cagA− genotype was detected in the corpus in two patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other methods of treatments have also received recognition across the globe. The limitation, however, is that different strains exhibiting different drug resistance and susceptibility patterns have been isolated from a single patient from several locations [ 82 86 ].…”
Section: An Overview Of H Pylori Infectionmentioning
confidence: 99%
“…For more information, a review paper by Roszczenko-Jasinska et al [ 87 ] is recommended. In addition, the co-infection with multiple H. pylori strains, which may have different genotypes and phenotypes, has been observed within the same patient [ 86 ]. Such genetic variability proves drug susceptibility therapy difficult and poses the danger of the evolution of more virulent and adapted strains.…”
Section: An Overview Of H Pylori Infectionmentioning
confidence: 99%